Razvoj postsovjetskega političnega diskurza od perestrojke do Putina - Uhlik, Mladen (Monitor ISH, 2004)
The development of post-Soviet political discourse: from perestroika to Putin. The study presents some general aspects of the relation between the political discourse and the political situation in the Russian Federation of the last decade. The first part tackles the period of "democratisation" in the nineties, outlining some ideal representations of this period, such as glasnost, freedom of speech, active dialogue between politicians and their addressees, and the pluralism of political choices. The second part treats the changes in the political situation and discourse after the ascendance of Vladimir Putin, whose policy has resulted in a reduction of the political arena. The study analyses his political discourse. His populist discursive strategies are often based on the breaking of cooperative principles, which produces a strong perlocutionary effect.
Keywords: politični diskurz; diskurzivne strategije; populizem; politična komunikacija; politični akterji; Rusija